Adaptation of a simple dipstick test for detection of Vibrio cholerae O1 and O139 in environmental water - Chakraborty, Subhra; Alam, Munirul; Scobie, Heather M.; Sack, David A. (Frontiers in Microbiology, 2013)
The presence of Vibrio cholerae in the environment is key to understanding the epidemiology of cholera. The gold standard for laboratory confirmation of V. cholerae from water is a culture method, but this requires laboratory infrastructure. A rapid diagnostic test that is simple, inexpensive, and can be deployed widely would be useful for confirming V. cholerae in samples of environmental water. Here, we evaluated a dipstick test to detect V. cholerae O1 and O139 from environmental water samples in spiked samples and under field conditions. When environmental water samples were incubated in alkaline peptone water for 24 hours at room temperature, samples spiked with as few as 10 CFU could be detected using the dipstick test. When compared to culture, the test was 89% sensitive and 100% specific with environmental samples.